Improving phenotypic prediction in dairy cattle breeding using the metagenome - González Recio, Oscar (2019)
González-Recio O., Saborío-Montero A., López-García A., Delgado B. Ovilo C. 2019. Improving phenotypic prediction in dairy cattle breeding using the metagenome. Chapter 9 in the book: Advances in breeding of dairy cattle. Burleigh Dodds Science Publishing Limited. pp:480.